2019
DOI: 10.1002/jcb.28711
|View full text |Cite
|
Sign up to set email alerts
|

Impact of bedaquiline and capreomycin on the gene expression patterns of multidrug‐resistant Mycobacterium tuberculosis H37Rv strain and understanding the molecular mechanism of antibiotic resistance

Abstract: The emergence of multidrug resistance (MDR), extensively drug‐resistant, and total drug‐resistant Mycobacterium tuberculosis (Mtb) strains have hampered the treatment of tuberculosis (TB). Capreomycin and Bedaquiline are currently used for MDR‐TB treatment. To understand the impact of these antibiotics on Mtb genes, we have curated the gene expression data where the Mtb cultures were exposed to the Bedaquiline and Capreomycin. Based on the P value cut off (<0.05) and logFC (<−0.5 and >+0.5) values, we have sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Similarly, Miryala et al. (2019) performed gene interaction network analysis and enrichment analysis and reported rpoB, rpsL, gyrA and gyrB in one cluster as antibiotic resistant genes with high number of functional interactors that may play the key role in pathogenic virulence and antibiotic resistance. embA, embB and embC are the key enzymes responsible for biogenesis of arabinogalactan and lipoarabinomannan, the two major constituents of the mycobacterial cell wall (Singh et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Miryala et al. (2019) performed gene interaction network analysis and enrichment analysis and reported rpoB, rpsL, gyrA and gyrB in one cluster as antibiotic resistant genes with high number of functional interactors that may play the key role in pathogenic virulence and antibiotic resistance. embA, embB and embC are the key enzymes responsible for biogenesis of arabinogalactan and lipoarabinomannan, the two major constituents of the mycobacterial cell wall (Singh et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The interactions between rpoA, rpoB and rpoC subunits are known, and it had been proposed that rpoB mutations in rifampicin-resistant Mtb mutants come with a fitness cost while mutations in rpoA or rpoC are F I G U R E 7 Bipartite graph represents the rpoC gene and relevant source mutations and chromosome position; blue circles represent the amino acids mutations proposed to compensate this fitness cost(Xu et al, 2018). Similarly,Miryala et al (2019) performed gene interaction network analysis and enrichment analysis and reported rpoB, rpsL, gyrA and gyrB in one cluster as antibiotic resistant genes with high number of functional interactors that may play the key role in pathogenic virulence and antibiotic resistance. embA, embB and embC are the key enzymes responsible for biogenesis of arabinogalactan and lipoarabinomannan, the two major constituents of the mycobacterial cell wall(Singh et al, 2019).…”
mentioning
confidence: 99%
“…PCa gene expression data (RNA-Seq) and the corresponding clinical data were downloaded from the TCGA database (https:// portal.gdc.cancer.gov) and Gene Expression Omnibus (GEO: https://www.ncbi.nlm.nih.gov/geo/). With |log 2 (fold change)| >0.5 and false discovery rate (FDR) <0.05 as the standards (22), the data were standardized with the "edgeR" package of R software (version 3.6.3, https://www.r-project.org), and then differential expression analysis was performed. The glycolysis-related gene dataset was downloaded from GSEA (http://www.…”
Section: Collection Of Prostate Cancer Datamentioning
confidence: 99%
“…A recent study demonstrated that deletion of cpnB , which encodes a multifunctional protein that hydrolyzes c-di-AMP, c-di-GMP, and nanoRNAs, upregulated all the cas (CRISPR-associated) genes compared to the WT ( Zhang et al, 2018 ). Of note, the expression of cas gene varies in response to environmental stresses, such as oxidative stress and antibiotic treatment ( Miryala et al, 2019 ), suggesting a link between the activity of type III-A CRISPR-Cas and stresses. Indeed, it has been reported that overexpression of cas genes impacts mycobacterial physiology ( Huang et al, 2016 ; Zhai et al, 2018 ; Wei et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%